Accelerated (45 mW/cm2) Transepithelial Corneal Cross-Linking for Progressive Keratoconus Patients: Long-Term Topographical and Clinical Outcomes - Zhang, Xiaoyu; Sun, Ling; Tian, Mi; Shen, Yang; Li, Meiyan; Zhao, Jing; Zhou, Xingtao (Frontiers in Medicine, 2020)
Aims To investigate the long-term clinical outcomes of accelerated (45 mW/cm2) transepithelial corneal cross-linking (ATE-CXL) for the treatment of keratoconus. Methods Fourty-two eyes (37 patients) treated for keratoconus were enrolled. The preoperative mean maximum keratometry (Kmax) value was 57.29 ± 9.13 diopters (D) and the thinnest corneal thickness (TCT) was 456.21 ± 44.66 μm. ATE-CXL was performed using riboflavin and pulsed-light ultraviolet treatment (45 mW/cm2, 7.2 J/cm2). Structural and functional measurements were performed at 1-week, and 1-, 3-, 6-, 12-, 24-, 36-, 48-months postoperatively. Results Surgery was uneventful in all eyes. Mean uncorrected (UDVA) and corrected distance visual acuity (CDVA) (logMAR) were 0.99 ± 0.58 and 0.44 ± 0.27 (P = 0.022), 0.24 ± 0.29 and 0.27 ± 0.35 (P = 0.601), at baseline and last follow-up, respectively. Mean Kmax were 56.67 ± 9.36 at 4-years postoperatively (P = 0.781). TCT changed to 453.17 ± 46.76 by 4-years postoperatively (P = 0.780). Corneal parameters, including topography value, ECD, and refractive errors were stable at 4-years postoperatively. No complications were observed during follow-up. Conclusion ATE-CXL was shown to be effective and safe for the treatment of keratoconus. Clinical efficiency of ATE-CXL in progressive keratoconus patients with thin corneal thickness and high PCE value need more investigation.